1, 2, 3‐triazole crosslinked polymers as binders for solid rocket propellants. Issue 15 (7th March 2014) - Lee, Dong‐Hoon; Kim, Kyoung Tae; Jang, Yujin; Lee, Sookyeong; Jeon, Heung Bae; Paik, Hyun‐jong; Min, Byoung Sun; Kim, Wonho
ABSTRACT In this study, 1, 2, 3‐triazole crosslinked polymers were synthesized as a new binder for solid rocket propellant systems by reacting the azide groups of the polymer with the ethynyl groups of a dipolarophile curing agent. All the mixtures were cured in an oven at 52°C for 7 days, and the curing reactivity of the products was analyzed using a Fourier transform‐infrared spectrometer. The carbonyl group adjacent to the triple bond, which acts as an electron‐withdrawing group, considerably accelerated the 1, 3‐dipolar cycloaddition reaction between the azide and ethynyl functional groups, affording rubbery materials. The modulus of the polymers increased whereas the elongation at the break decreased with increasing ratio of the crosslinker to the prepolymer, resulting in highly crosslinked polymers. The molecular weights between the crosslinking points and interaction parameters of the 1, 2, 3‐triazole crosslinked polymers were determined from the swelling data, Flory–Rehner equation, and Mooney–Rivlin equation. © 2014 Wiley Periodicals, Inc. J. Appl. Polym. Sci. 2014, 131, 40594.